2006
DOI: 10.1016/j.tibs.2006.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Folding of small disulfide-rich proteins: clarifying the puzzle

Abstract: The process by which small proteins fold to their native conformations has been intensively studied over the last few decades. In this field, the particular chemistry of disulfide bond formation has facilitated the characterization of the oxidative folding of numerous small, disulfide-rich proteins with results that illustrate a high diversity of folding mechanisms, differing in the heterogeneity and disulfide pairing nativeness of their intermediates. In this review, we combine information on the folding of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
160
0
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 164 publications
(171 citation statements)
references
References 77 publications
(59 reference statements)
5
160
0
6
Order By: Relevance
“…The physiological relevance of those results were recently confirmed in mammalian cells in vivo, where the GSH pool was shown fundamental for the efficient import of Cox19 and other Mia40 substrates (22). Low amounts of reducing agents are known to increase oxidative folding rates acting as thiol catalysts by counteracting the accumulation of partially oxidized non-native isomers (23). In Fig.…”
Section: Oxidative Folding Of Cox19 Involves the Formation Of Native mentioning
confidence: 65%
“…The physiological relevance of those results were recently confirmed in mammalian cells in vivo, where the GSH pool was shown fundamental for the efficient import of Cox19 and other Mia40 substrates (22). Low amounts of reducing agents are known to increase oxidative folding rates acting as thiol catalysts by counteracting the accumulation of partially oxidized non-native isomers (23). In Fig.…”
Section: Oxidative Folding Of Cox19 Involves the Formation Of Native mentioning
confidence: 65%
“…These studies revealed that both species comprise three native disulfide bonds in one domain and no disulfide bonds in the other domain. IIIa: Cys 3 Table 1 and the MS spectra in the supplemental materials.…”
Section: Resultsmentioning
confidence: 99%
“…Understanding the sequence of folding events in proteins may not only help to predict protein structures from amino acid sequences but also provide invaluable information to a variety of related fields, such as protein design or protein misfolding associated with pathological diseases (1,2). A number of studies concerning folding have been focused on small, disulfide-rich proteins, given that the chemistry of disulfide bond formation allows the trapping and subsequent characterization of the folding intermediates that accumulate, something difficult to attain with disulfide-free proteins (3,4). In oxidative folding, reduced and denatured proteins are allowed to recover both its native disulfide bonds and native structures in the absence or presence of redox agents.…”
mentioning
confidence: 99%
“…Fig. 7 summarizes the OaPDI-assisted folding pathways of the linear and cyclic peptides in the form of a folding funnel diagram (41,42). After 24 h, the peptides are mainly oxidized and have folded either into their native disulfide connectivities, which occupy the lowest energy levels in the folding funnel or are trapped in higher energy wells as nonnative three-disulfide species.…”
Section: Retention Timementioning
confidence: 99%